2021
DOI: 10.1101/2021.01.06.425641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuron-type specificity of dorsal raphe projections to ventral tegmental area

Abstract: The midbrain dorsal raphe (DR) and ventral tegmental area (VTA) contain two of the brains main ascending neuromodulatory transmitters: serotonin and dopamine. We studied the pathway from DR to VTA using single-cell RNA sequencing, anatomical tracing, and electrophysiology and behavior in mice. Single-cell sequencing confirmed a differential distribution of dopamine cell types between medial and lateral aspects of the VTA. This molecular diversity included differential expression of a subset of glutamatergic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…In contrast, we find that many DRN neurons positively signal offer value and RPEs, which strikingly resembles the responses of midbrain DA neurons in the ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) [60][61][62] . This is broadly consistent with previous observations of DRN neurons that code reward-related variables positively -some reporting a mix of positive and negative coding neurons 27,[34][35][36]70 and others reporting predominantly positive 29,30,117,127,128 -and with recent findings that DRN may contribute to VTA RPE signals through monosynaptic projections onto DA neurons 129 . While these results do not rule out the possibility that certain subpopulations of neurons in subregions of DRN 91 or other 5-HT nuclei 130 may indeed play an opponent role to DA, they suggest a new, potentially cooperative relationship between the 5-HT and DA systems 131 .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, we find that many DRN neurons positively signal offer value and RPEs, which strikingly resembles the responses of midbrain DA neurons in the ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) [60][61][62] . This is broadly consistent with previous observations of DRN neurons that code reward-related variables positively -some reporting a mix of positive and negative coding neurons 27,[34][35][36]70 and others reporting predominantly positive 29,30,117,127,128 -and with recent findings that DRN may contribute to VTA RPE signals through monosynaptic projections onto DA neurons 129 . While these results do not rule out the possibility that certain subpopulations of neurons in subregions of DRN 91 or other 5-HT nuclei 130 may indeed play an opponent role to DA, they suggest a new, potentially cooperative relationship between the 5-HT and DA systems 131 .…”
Section: Discussionsupporting
confidence: 92%
“…Together, these results suggest that a greater appreciation of parallel sensorimotor pathways will continue to be critical for models of conditioned approach behavior (Nicola, 2010(Nicola, , 2016. In both trace-conditioning paradigms (Brown et al, 2014;Chang et al, 2021;Cohen et al, 2012;Pan et al, 2013) as well as in self-stimulation paradigms (Steffensen et al, 2001), mGABA neurons are active around the time of conditioned approach and give rise to dense projections to premotor regions of mesencephalon (Dudman and Gerfen, 2015). Previous work has shown shorter latency (10-30 ms) phasic activity of non-DA midbrain neurons that also correlates with the predictive and incentive properties of cues (Pan and Dudman, 2015;Pan et al, 2013;Schmidt et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, predictive cues elicit rapid, learning-dependent responses in non-DA (midbrain GABAergic [mGABA]) neuron activity in the VTA at a shorter latency ($10-30 ms; Pan and Dudman, 2015;Pan et al, 2013). In afferent stimulation experiments, we recorded from a large population of VTA neurons (>300) that included 40 putative mDA units (identified based upon characteristic response criteria; Chang et al, 2021;Cohen et al, 2012;Pan et al, 2013), 13 of which were also activated at short latency by stimulation of afferent inputs (Figure 4F). Importantly, after behavioral acquisition of MFC ChR2+ stimulation as a predictive cue, we observed a characteristic long-latency ($45 ms) mDA VTA neuron response that closely matched the latency of phasic responses to predictive auditory cues (Figures 4E and S7)-even in mDA neurons lacking direct input from the stimulated inputs.…”
Section: Cell Reportsmentioning
confidence: 99%
“…Some have shown that serotonergic DRN neurons play a key modulatory role in reward processing (Browne et al, 2019;Liu et al, 2020;Luo et al, 2015;Nagai et al, 2020;Ren et al, 2018), while dopaminergic DRN neurons appear to encode the motivational salience of incentives (Cho et al, 2021). Additionally, serotonergic DRN neurons project to the dopamine-rich ventral tegmental area (VTA) (Chang et al, 2021;Gervais & Rouillard, 2000), revealing its potentially crucial role in providing a more comprehensive understanding of mutual inhibition between DA and 5-HT.…”
Section: Mutual Inhibition Between Dopamine and Serotonin In The Dorsal Raphé Nucleusmentioning
confidence: 99%